EFFECT OF PROCESSING METHODS ON CHEMICAL AND NUTRIENT COMPOSITION OF BAMBOO (Bambusae arundinacea) LEAVES - O. F. Akinmoladun (Journal of Animal and Plant Sciences, 2022)
Due to their abundant macro and micronutrients, some leaves hold a lot of promise as potential forage plants for livestock. However, a major limitation is the high content of anti-nutritional factors that combine with nutrients and reduce their bioavailability. This study, therefore, aimed to evaluate the effect of processing on the chemical and nutrient composition of bamboo leaves. The leaves were subjected to four different physical processing methods; T1 (control, air drying), T2 (fermenting in an airtight bag for five days), T3 (soaking in ordinary water for 24 h), and T4 (soaking in warm water at 50 oC for 20 min). Fresh samples of the leaf were also analyzed on a wet basis (T5). Samples from respective treatment groups were analyzed for proximate composition, mineral constituents, anti-nutritional factors, vitamin C, flavonoids and antioxidant activities following standard procedures. The values obtained were subjected to a one-way analysis of variance using the generalized linear model of SAS. Although there was no significant effect of processing on ether extract and crude fiber, the crude protein content was significantly higher (P≤0.05) for T3 and T4. The ash content was lowest (P≤0.05) in T3 compared to other treatment groups. The fiber fractions (acid detergent lignin, neutral detergent fiber, hemicelluloses and cellulose) were highest (P≤0.05) in T1 than other treatment groups. T1 had the lowest (P≤0.05) for phosphorous and potassium. However, T2, T3 and T4 had similar (P>0.05) phosphorous and sodium compositions. The processing effect was not significant (P>0.05) on vitamin C, alkaloids, saponins, and tannin. However, the phytate was highest (P≤0.05) in T1. The physical processing of bamboo leaves lowers the antinutrient appreciably without adversely affecting the proximate composition. Further, the high nutrient composition of bamboo leaves, irrespective of processing methods, attests to its potential as an important forage plant.
Keywords: Antinutrients; bamboo leaves; fiber fractions; processing; proximate